3(2x+1)+5=25

Simple and best practice solution for 3(2x+1)+5=25 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+1)+5=25 equation:


Simplifying
3(2x + 1) + 5 = 25

Reorder the terms:
3(1 + 2x) + 5 = 25
(1 * 3 + 2x * 3) + 5 = 25
(3 + 6x) + 5 = 25

Reorder the terms:
3 + 5 + 6x = 25

Combine like terms: 3 + 5 = 8
8 + 6x = 25

Solving
8 + 6x = 25

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 6x = 25 + -8

Combine like terms: 8 + -8 = 0
0 + 6x = 25 + -8
6x = 25 + -8

Combine like terms: 25 + -8 = 17
6x = 17

Divide each side by '6'.
x = 2.833333333

Simplifying
x = 2.833333333

You can always share this solution

See similar equations:

| 3x=x+1 | | 12j=16j-128 | | -2.89=1.7m | | 3y+10=-23 | | 4x+3x+5+2=56 | | x^2-24x-25=0 | | 7+4k-6= | | 25=3(x-7)+5 | | 8(1+r)=1+8r | | 8n(6n+7)=5 | | 4r+3r= | | 13x^2-8x=0 | | (y-7)-(y+4)=8y | | 3x^2-75=0 | | 5(x-2)=7x | | 3(x+3)+5=25 | | 18.03=3g+3.72 | | 9b+7-1= | | 10x-16=74 | | 1.32g-8=0.58 | | 6(5+7z)= | | 9x+8=71 | | 42=8m-13m | | 2(-x-1)=2x-34 | | 3(x-1)+5=25 | | 5(-7z-6)= | | 49x^2-196=0 | | 5t-0=-3t+7 | | 3(-14+2)=4(5-14) | | -5(n+8)=-98 | | 4g+3g+9g= | | x^2-13x=-30 | | 4(3x-2)=52 | | 5x^2-24x+18=0 | | 3x^2-6x+45=0 | | x^2-13=-30 | | 32+5(8.6)=n | | 5r+r+4r= | | 24=5x+6-2x | | 11r-6r+5r=168 | | 32+5(8.6)= | | 3(-14+2)=4(5-13) | | 3y+10=9 | | 3m-4=2m-13 | | 41+8z=-z^2 | | 8x+12=100 | | b-3+3b=36 | | 3y+7=9 | | 4(y+2)=5(y-5) | | 6x-10=-18x-4 | | 3x^2-15x+45=0 | | 2(-2+x)-1(x-4)=0 | | (x-6)(5x+3)=0 | | 27=y | | (x+3)(6x+7)=0 | | 2y-8=-y+4 | | 6x^2-8x+3=0 | | 0=-5h-2h | | 4h*6h= | | -2+2y=-4 | | 3-4r=10r+10 | | (3m-4n-7)-(8m+n-6)= | | 32+5n=75 | | 2y=4x-3 | | 2+11x=12x-6 |

Equations solver categories